The Effect of Perfectionism on Academic Procrastination among Thesis-Writing Students: The Mediating Role of Fear of Failure - Zahro, Azimatus; Widyana, Rahma (Journal of Educational, Health and Community Psychology, 2025)
This study aims to determine the effect of perfectionism on academic procrastination behavior mediated by fear of failure in students writing theses. Maladaptive perfectionism often encourages the emergence of fear of failure, which then triggers the tendency to delay completing tasks. This study uses a quantitative approach with the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The subjects of the study consisted of 270 students writing theses in Indonesia. Using PLS-SEM (N = 270; bootstrapping 5,000), perfectionism showed a direct effect on academic procrastination (β = 0.667, 95% CI [0.575-0.754]) and an indirect effect via fear of failure (β = 0.353, 95% CI [0.203-0.502]), indicating partial mediation. Model fit was acceptable (SRMR = 0.068); measurement quality satisfied reliability and validity criteria (CR, AVE, HTMT). This finding strengthens the assumption that the higher the level of perfectionism possessed by students, the greater the likelihood that they will experience fear of failure and delay completing tasks as a form of avoidance. Therefore, it is important for educational institutions and educators to help students manage perfectionism and fear of failure in order to suppress academic procrastination behavior.